Screening of Active Compounds Against Porcine Epidemic Diarrhea Virus in Hypericum japonicum Thunb. ex Murray Extracts - Hongyu Rao; Siqi Liu; Hao Wu; Wenlong Wang; Weiyue Wang; Weiwei Su; Peibo Li (Viruses, 2025)
Porcine epidemic diarrhea (PED) remains a persistent threat to global swine production, necessitating urgent development of targeted interventions. Our previous research established that Hypericum japonicum Thunb. ex Murray (HJT) extract exhibited significant anti-porcine epidemic diarrhea virus (PEDV) activity both in vivo and in vitro. Nevertheless, the principal bioactive constituents mediating this antiviral activity remained uncharacterized. In this study, it was demonstrated that ethanol eluates with 20% (v/v) and 60% (v/v) ethanol exhibited activity against PEDV. Phytochemical characterization revealed 66 distinct compounds, including 36 flavonoids and 13 organic acids identified as possible antiviral constituents. Among these, taxifolin-7-O-rhamnoside and quercetin-7-rhamnoside were identified as the most potent anti-PEDV components. Notably, neither compound exhibited significant antiviral efficacy as monotherapy. However, co-administration produced a reduction in PEDV-G2 titers. This study mechanistically links taxifolin-7-O-rhamnoside and quercetin-7-rhamnoside as core anti-PEDV phytochemicals in HJT extract. These findings support the further development of HJT as a potential therapeutic for PED.